Analisis Pengendalian Kualitas dengan Menggunakan Metode SQC untuk Meminimumkan Produk Cacat - Maulud, Ilham; Gumelar, Eka Tresna (UNISBA Press, 2023)
Abstract. Demada Collection Convection is a convection engaged in the convection of gamis clothes which in its production activities is still minimal on quality control so that there are still many defective products. The purpose of this research is to find out how the controls carried out by the Demada Collection Convection, and analyze using the statistical quality control (SQC) method. In this research, the research method uses descriptive quantitative with data collection techniques, namely observation, interviews, and documentation. In collecting data, it starts with making check sheets, histograms, scatter charts, pareto charts, np control charts, and fishbone charts. The results of the study show that there are three types of defects that are often encountered, namely less neat stitches, torn buttonholes, and less strong buttons. Fishbone chart provides the causes of defects in production, including machine, method, human, and media (environment) factors. The Pareto chart provides data on the dominant type of damage, namely the less neat stitches that provide 36% of the total defects and the results of the analysis of the control chart show deviations from the special cause of variation in quality control at Demada Collection Convection which is caused by not having a clear SOP. To reduce defective products produced, Standard Operating Procedures (SOPs) are needed, conduct training for employees, perform maintenance on machines, and also add lighting to the production room. Abstrak. Konveksi Demada Collection merupakan konveksi yang bergerak dibidang konveksi baju gamis yang dalam kegiatan produksinya masih minim terhadap pengendalian kualitas sehingga masih terdapat banyak produk cacat. Tujuan dari penelitan ini untuk mengetahui bagaimana pengendalian yang dilakukan oleh Konveksi Demada Collection, serta menganalisis menggunakan metode statistical quality control (SQC). Pada penelitian kali ini metode penelitian menggunakan deskriptif kuantitatif dengan teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Dalam pengumpulan data dimulai dengan membuat check sheet, histogram, scatter chart, pareto chart, control chart np, dan fishbone chart. Hasil dari penelitian menunjukkan adanya tiga jenis cacat yang sering ditemui, yakni jahitan kurang rapih, lubang kancing robek, dan kancing kurang kuat. Fishbone chart memberikan penyebab kecacatan pada produksi, diantaranya adalah dari faktor mesin, metode, manusia, dan juga media (lingkungan). Pareto chart memberikan data jenis kerusakan yang dominan yakni jahitan kurang rapih memberikan 36% dari total cacat dan hasil analisis dari control chart menunjukkan penyimpangan special cause of variation pada pengendalian kualitas di Konveksi Demada Collection yang disebabkan karena tidak memiliki SOP yang jelas. Untuk mengurangi produk cacat yang diproduksi diperlukan Standar Operasional Prosedur (SOP), melakukan pelatihan pada karyawan, melakukan perawatan pada mesin, dan juga menambah penerangan pada ruangan produksi.